Biological psychology - Kalat, James W. (Wadsworth, 2013)
The textbook retains the hallmark approach of this respected text, whilst presenting the content in a print and digital hybrid that has been tailored to meet the rapidly developing demands of today's lecturers and students. This blended solution offers a streamlined textbook for greater accessibility and convenience, complemented by a bolstered online presence, for a truly multi-faceted learning experience. Now in its eleventh edition, this excellent text provides an extremely high level of scholarship combined with a clear and occasionally humorous writing style, and precise examples.